2014
DOI: 10.1159/000360603
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review on the Quality of Life Benefits after Percutaneous Coronary Intervention in the Elderly

Abstract: Aims: Percutaneous coronary intervention (PCI) is being increasingly performed on elderly patients with acceptable peri-procedural outcomes and long-term survival. We aim to systematically review the health-related quality of life (HRQOL) following PCI in the elderly which is an important measure of procedural success. Methods: A systematic review of clinical studies before September 2012 was performed to identify HRQOL in the elderly after PCI. Strict inclusion and exclusion criteria were applied. Quality app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…2) elderly patients experienced similar improvement in selfreported HRQOL after PCI compared with younger patients; 3) improvement in HRQOL was sustained up to 36 months in all age groups; and 4) poor baseline HRQOL, STEMI, and MIB in 6 months were independent predictors of significant long-term improvement in HRQOL after PCI. Our results were consistent with a systematic review of 11 studies that demonstrated improved HRQOL in elderly patients after PCI for at least 1 year across a broad range of health domains, and that older patients improved as much as younger patients, especially in the areas of physical functioning and angina status [28]. In one study, octogenarians who underwent PCI experienced greater improvement in role physical and bodily pain at 6-month follow-up compared with younger patients [29].…”
Section: Discussionsupporting
confidence: 89%
“…2) elderly patients experienced similar improvement in selfreported HRQOL after PCI compared with younger patients; 3) improvement in HRQOL was sustained up to 36 months in all age groups; and 4) poor baseline HRQOL, STEMI, and MIB in 6 months were independent predictors of significant long-term improvement in HRQOL after PCI. Our results were consistent with a systematic review of 11 studies that demonstrated improved HRQOL in elderly patients after PCI for at least 1 year across a broad range of health domains, and that older patients improved as much as younger patients, especially in the areas of physical functioning and angina status [28]. In one study, octogenarians who underwent PCI experienced greater improvement in role physical and bodily pain at 6-month follow-up compared with younger patients [29].…”
Section: Discussionsupporting
confidence: 89%
“…Recently, a large multinational registry revealed no difference in death, stroke or MI among octogenarians revascularized with PCI versus CABG surgery at a median follow-up of 1088 days [ 19 ]. Moreover, a systematic review of clinical studies performed to identify the health-related quality of life (HRQOL) after PCI in the elderly, showed that they have significant improvements in cardiovascular well-being after PCI [ 20 ]. Another recent study conducted in octogenarians, also exhibited the benefits of PCI in a cohort of 353 consecutive patients with ACS [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Older age, obesity, diabetes, and coexisting hypertension or hyperlipidemia are the main risk factors of CAD [ 5 ]. Their high prevalence and increasingly improving therapeutic methods will increase the necessity for therapeutic decisions regarding strategies for treating acute coronary syndrome (ACS) and stable coronary artery disease (CAD) in older populations [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%